Effect of Chitosan and Cationic Polyacrylamide on Optical and Mechanical Properties of Paper Made from Chemi-Mechanical Pulps - Hatef Heydari; Ramin Vaysi; Abdolla Hosseinzadeh; Reza Bakhshi; Majid Kiaei (BioResources, 2024)
The influences of nano-chitosan and cationic polyacrylamide (cPAM) on the optical and mechanical properties of paper made from chemi-mechanical pulp (CMP) were investigated. Bleached chemi-mechanical pulp (CMP) was selected as the control sample. The cPAM was considered at four levels (0%, 0.25%, 0.5%, and 0.75%), while chitosan was added to the CMP suspension at three levels (0%, 1%, and 2%). Paper test specimens were prepared according to TAPPI standards with a basis weight of 60 g/m2, and their optical and mechanical properties were measured. The results indicated that the opacity, greenness, tear strength, burst strength, and Gurley seconds were increased, whereas brightness, water absorption, and a* factor were decreased by increasing the amount of cPAM. Adding chitosan to CMP increased the a* factor, tear strength, breaking length, burst strength, Gurley seconds, water absorption, and greenness in the resulting paper. When polyacrylamide and nano-chitosan were added simultaneously to CMP, the brightness, water absorption, and greenness of the resulting paper decreased, but opacity, burst strength, tear strength, and air resistance had an appropriate increase. In all treatments, the best results were found at 1% chitosan and 0.5% cPAM due to favorable optical and mechanical properties.